Innovation Strategies to Reduce SMEs’ Bankruptcy Prediction During COVID-19 Pandemic in Central Java - Ahmad Hijri Alfian (Jurnal Sosioteknologi, 2022)
As a result of the COVID-19 epidemic, the business sector, particularly SME’s, iscurrently undergoing turbulence. To combat this epidemic, SMEs doers must increasetheir efficiency and effectiveness and maximize their market share by leveragingpossibilities and innovative solutions. Prior to and during a pandemic, small andmedium-sized enterprises (SMEs) faced challenges that may have led to their bankruptcyrather than having a large influence on the national economy and the micro welfare.having The purpose of this study was to determine the effect of the innovation strategycarried out by SMEs in dealing with potential bankruptcy in the Covid-19 pandemicera. Innovation strategy is measured through “Cost Research and Development”, whilebankruptcy prediction is calculated using “Z Score Altman Model”. The research usedprimary data, namely financial data questionnaires, while the sample and researchpopulation were SMEs in the province of Central Java. The results show that theinnovation strategy is proven to be able to influence SMEs bankruptcy prediction, andits financial performance is proven to be a significant moderating variable which, if itshows good results, then it can weaken the bankruptcy prediction. Furthermore, thisinnovation strategy is also able to reduce the prediction of bankruptcy because it has apositive effect; the higher the innovation strategy, the higher the Z-Score value is, whilethe potential for bankruptcy prediction becomes smaller.